Microbial infection and treatment strategies in cancer patients - Zhu, Kejing; Yuan, Zhibo; Li, Jingli; Fu, Ailing (Frontiers in Microbiology, 2025)
The interplay between microbes and cancer has garnered significant attention in life sciences. Clinically, microbial infections in cancer patients are common complications and one of the major causes of mortality. Cancer patients often experience compromised immune defenses, and conventional therapies—including radiotherapy, chemotherapy, and invasive surgery—further diminish their resistance to pathogens. Emerging evidence indicates that intratumoral microbes and their interactions with the tumor microenvironment exacerbate cancer cell proliferation, drug resistance, metastasis, and poor prognosis. However, complex multidrug regimens increase patient burden and reduce compliance. This necessitates the development of single agents with dual anticancer and antimicrobial properties. Promisingly, naturally derived compounds and synthetic chemicals exhibit such dual functionalities. This review introduces microbial contributions to oncogenesis and analyzes molecular targets of dual-function agents, proposing their potential as novel therapeutics to improve clinical outcomes.